2012
DOI: 10.1007/s10995-012-1210-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Pre-pregnancy Weight Versus Weight Measured at First Prenatal Visit: Effects on Categorization of Pre-pregnancy Body Mass Index

Abstract: Objectives To compare classification of pre-pregnancy body mass index (BMI) using self-reported pre-pregnancy weight versus weight measured at the first prenatal visit. Methods Retrospective cohort of 307 women receiving prenatal care at the faculty and resident obstetric clinics at a Massachusetts tertiary-care center. Eligible women initiated prenatal care prior to 14 weeks gestation and delivered singleton infants between April 2007 and March 2008. Results On average, self-reported weight was 4 pounds l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 29 publications
3
69
1
Order By: Relevance
“…33,34,42 As reported in a prior study, self-reported weight was on average 1.8 kg lighter than weight measured at initiation of prenatal care. 48 Underestimation of pre-pregnancy weight will result in the overestimation of PPWR. While measuring pre-pregnancy weight is often not possible in the clinical setting, researchers should measure a woman's weight in the postpartum period to derive a better and more accurate measurement of PPWR.…”
Section: Discussionmentioning
confidence: 99%
“…33,34,42 As reported in a prior study, self-reported weight was on average 1.8 kg lighter than weight measured at initiation of prenatal care. 48 Underestimation of pre-pregnancy weight will result in the overestimation of PPWR. While measuring pre-pregnancy weight is often not possible in the clinical setting, researchers should measure a woman's weight in the postpartum period to derive a better and more accurate measurement of PPWR.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study found that self-reported and clinically measured prepregnancy weight are highly correlated (r=0.99) and mean underreporting of weight by ~2 pounds did not differ by race/ethnicity, gestational age, or pre-pregnancy weight. 27 In a previous study derived from this patient population, categorization of pre-pregnancy BMI was identical for 87% of women when using self-reported pre-pregnancy weight or weight measured at first prenatal visit during the first trimester; 28 thus, potential misclassification is unlikely to alter our findings. Given the modest number of women with class II or III obesity with whom vacuum-assisted vaginal delivery was attempted (N=240) and the small number of obese women with attempted vacuum-assisted vaginal delivery that was not successful (N=9), we were unable to examine rates of attempted or successful vacuum-assisted vaginal delivery in relation to class of obesity.…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, some investigators have observed that self-reported pre-pregnancy weight and weight measured at the first prenatal visit result in identical classification of pre-pregnancy BMI status. [30][31][32] It is common to evaluate self-reported pre-pregnancy data in order to avoid possible changes in weight occurring during the first trimester of pregnancy. Most women come for their first antenatal visit early in their pregnancy, that is, before the 12th week.…”
Section: Discussionmentioning
confidence: 99%